Mixed Linkage β-1,3/1,4-Glucan Oligosaccharides Induce Defense Responses in Hordeum vulgare and Arabidopsis thaliana - Barghahn, Sina; Arnal, Gregory; Jain, Namrata; Petutschnig, Elena; Brumer, Harry; Lipka, Volker (Frontiers in Plant Science, 2021)
Plants detect conserved microbe-associated molecular patterns (MAMPs) and modified “self” molecules produced during pathogen infection (danger associated molecular patterns (DAMPs)) with plasma membrane-resident pattern recognition receptors (PRRs). PRR-mediated MAMP and / or DAMP perception activates signal transduction cascades, transcriptional reprogramming and plant immune responses collectively referred to as pattern-triggered immunity (PTI). Potential sources for MAMPs and DAMPs are microbial and plant cell walls, which are complex extracellular matrices composed of different carbohydrates and glycoproteins. Mixed linkage β-1,3/1,4-glucan (β-1,3/1,4-MLG) oligosaccharides are abundant components of monocot plant cell walls and are present in symbiotic, pathogenic and apathogenic fungi, oomycetes and bacteria, but have not been detected in the cell walls of dicot plant species so far. Here, we provide evidence that the monocot crop plant H. vulgare and the dicot A. thaliana can perceive β-1,3/1,4-MLG oligosaccharides and react with prototypical PTI responses. A collection of Arabidopsis innate immunity signaling mutants and > 100 Arabidopsis ecotypes showed unaltered responses upon treatment with β-1,3/1,4-MLG oligosaccharides suggesting the employment of a so far unknown and highly conserved perception machinery. In conclusion, we postulate that β-1,3/1,4-MLG oligosaccharides have the dual capacity to act as immune-active DAMPs and/or MAMPs in monocot and dicot plant species.